MEDIASTINAL ENTERIC CYST: AN UNCOMMON CAUSE OF RECURRENT LOWER RESPIRATORY TRACT INFECTIONS IN CHILDREN - Kirovski, Ilija; Nonkulovski, Danilo (Journal of Morphological Sciences; Vol 5 No 3 (2022): JMS, 2022)
Enteric cysts in posterior mediastinum are rare congenital anomalies in children. A wide range of clinical manifestations can be found ranging from absence of symptoms to life threatening respiratory distress. We report a child case who had recurrent lower respiratory tract infections due to mediastinal enteric cyst accompanied by vertebral defects. A 6-year-old girl presented to the Clinic with a history of cough, fever and left chest pain. She had recurrent episodes of lower respiratory tract infections in the past. On physical examination no breath sounds were heard over the left chest. Chest x-ray revealed a left upper lobe atelectasis . A chest computed tomography scan showed a cystic mass in the left posterior mediastinum associated with cervicothoracic vertebral malformations. Thoracotomy was performed and the cyst was excised. Histopathology report revealed the diagnosis of enteric cyst. The patient recovered well from the surgery and was free of respiratory symptoms after that. Although mediastinal enteric cysts are uncommon conditions, it is essential to be considered in the differential diagnosis of respiratory distress among children. Clinicians should always keep in mind that the presence of associated cervical or thoracic vertebral anomalies may represent an important early clue to the diagnosis. The tendency of mediastinal enteric cyst to enlarge and cause subsequent respiratory distress is sufficient reason for early operative treatment and should be undertaken before the complications occur. Key words : Enteric cyst, lower respiratory tract infections, thoracotomy, children.